Tom Joad walking on the road - Thomas Hart Benton (artist):::Creator::::::::::::
Illustration of Tom Joad walking on the road from The Grapes of Wrath vol.1 p.20 illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate.The illustration pictures Tom walking home after the truck driver lets him off. "Joad took a few steps, and the flourlike dust spurted up in front of his new yellow shoes, and the yellowness was disappearing under the grey dust."